Colloquial Malay : - Othman, Zaharah (Routledge, 2007)
With this complete language course, you are just a few easy lessons away from gaining the confidence and ability to communicate in contemporary Malay. Let yourself be guided through the Malaysian culture, customs, politics, and trade while developing expert pronunciation. As Malay is spoken in some areas of Indonesia, this makes a perfect companion toColloquial Indonesian. This paperback in the Colloquial Language Learning Series is available individually here or as part of a cassette pack. To purchase the bookandthe cassettes, please refer to the cassette pack listing for this language.